ART THERAPY AND TRAUMATIC POST-WAR EXPERIENCE: AMERICAN PTSD STUDIES - Хрисанфова, Дарья; Кривуц, Светлана; Тарасов, Владимир (SWorldJournal, 2021)
Art therapy research is directly related to the problem of PTSD. According to the authors, the American experience with PTSD research is unique. PTSD therapy has been actively studied in the United States since the late 1970s. Thus, the research and empir